2019
DOI: 10.3390/nu11102409
|View full text |Cite
|
Sign up to set email alerts
|

Hypnotic Effects of Lactobacillus fermentum PS150TM on Pentobarbital-Induced Sleep in Mice

Abstract: The bidirectional communication between the gastrointestinal tract and the central nervous system appears to be functionally linked to the intestinal microbiome, namely the microbiome–gut–brain axis (MGBA). Probiotics with health benefits on psychiatric or neurological illnesses are generally called psychobiotics, and some of them may also be able to improve sleep by targeting the MGBA. This study aimed to investigate the effects of a psychobiotic strain, Lactobacillus fermentum PS150TM (PS150TM), on sleep imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 58 publications
2
20
0
Order By: Relevance
“…Our finding that the reduction in insomnia severity was complemented by the decrease in salivary cortisol levels, which might indicate possible correlations between probiotic use and sleep improvements through the HPA axis. This finding was in concordance with studies that have shown that some psychobiotics have sleep-improving effects in mice ( 62 ) or humans ( 63 , 64 ), but in contrast with another study that found that the psychobiotic strain JB-1 did not improve sleep compared to the placebo in healthy male volunteers ( 19 ). Previous studies have shown that cortisol may inhibit the syntheses of interleukin-1beta (IL-1β) or tumor necrosis factor alpha (TNF-α) ( 65 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our finding that the reduction in insomnia severity was complemented by the decrease in salivary cortisol levels, which might indicate possible correlations between probiotic use and sleep improvements through the HPA axis. This finding was in concordance with studies that have shown that some psychobiotics have sleep-improving effects in mice ( 62 ) or humans ( 63 , 64 ), but in contrast with another study that found that the psychobiotic strain JB-1 did not improve sleep compared to the placebo in healthy male volunteers ( 19 ). Previous studies have shown that cortisol may inhibit the syntheses of interleukin-1beta (IL-1β) or tumor necrosis factor alpha (TNF-α) ( 65 ).…”
Section: Discussionsupporting
confidence: 91%
“…However, excessive cytokines might still disturb the sleep structure ( 61 , 67 ). Other proposed explanations for the sleep-improving effects of PS128 TM on the regulation of wakefulness or sleep might be related to several neurotransmitters, such as the increase in GABA ( 68 ), decrease in orexin levels or increase in inhibitory adenosine levels in the ventrolateral preoptic nucleus, striatum, hypothalamus, hippocampus, and prefrontal cortex ( 62 , 69 ). Other non-invasive methods for monitoring changes in sleep stages may be required to clarify how PS128 TM affects the sleep structure among highly stressed individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Those with higher anxiety levels saw shorter average WASO and light sleep stage durations if taking HK-PS23. In line with previous studies that described improvements in sleep after probiotics use, 20,[56][57][58] reductions in the percentage of REM sleep, average time of WASO, and light sleep in our HK-PS23 group may be signs of increased quality of sleep. However, a lower total sleep time in our HK-PS23 group compared to the placebo does not necessarily mean that the participants did not have sufficient sleep.…”
Section: Papersupporting
confidence: 92%
“…At the genus level, a drastic decrease in the relative abundance of the genera Lactobacillus and Clostridium sensu stricto were detected in insomnia rats when compared with the controls. Lactobacillus species have been widely used as probiotics, which exhibit sleep-improving effects [ 27 ]. Additionally, the abundance of Lactobacillus and Clostridium sensu stricto were associated with the concentration of butyrate [ 28 ].…”
Section: Discussionmentioning
confidence: 99%